COST REDUCTION INNOVATION SEBAGAI BENTUK IMPLEMENTASI KAIZEN COSTING UNTUK COST COMPETITIVENESS DAN PENCAPAIAN TARGET PROFIT - Murtanto Murtanto; Andrea Utama (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This research describes how the implementation of Cost Reduction Innovation as a form of implementation of kaizen costing at PT. ABC, located in Jakarta.This research was conducted by direct observation, and the collection of related documents. For the measurement of research, on how well the implementation of Cost Reduction Innovation Activity, used four indicators, namely: 110% >achievement ratio (%) kaizen costing amount target (profit) > 90%, 110% > achievement ratio (%) kaizen costing per unit of product > 90%, 100% quantity ratio of implementing kaizen activities, and ratio (%) of cost saving per unit from kaizen activities to total cost saving per unit > 75%.The result of this research indicate that the implementation of Cost Reduction Innovation Activities at PT. ABC “Good”. This reflected on the achievement of three indicators, namely indicators of achievement ratio (% kaizen costing amount target (profit), indicators of achievement ratio (%) kaizen costing per unit of product, and ratio (%) of cost saving per unit from kaizen activities to total cost saving per unit. As for the quantity ratio indicator kaizen activity implementation has not been achieved.